2017
DOI: 10.3390/w9060403
|View full text |Cite
|
Sign up to set email alerts
|

Gridded Snow Water Equivalent Reconstruction for Utah Using Forest Inventory and Analysis Tree-Ring Data

Abstract: Snowpack observations in the Intermountain West are sparse and short, making them difficult for use in depicting past variability and extremes. This study presents a reconstruction of April 1 snow water equivalent (SWE) for the period of 1850-1989 using increment cores collected by the U.S. Forest Service, Interior West Forest Inventory and Analysis program (FIA). In the state of Utah, SWE was reconstructed for 38 snow course locations using a combination of standardized tree-ring indices derived from both FIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…analysis. In the study area, it is assumed that surficial groundwater levels peak at the same time as mountain snowpack, being around April 1 each year (Barandiaran et al 2017). Prior sewer flow data in the study area consistently indicated a spring high and a fall low.…”
Section: Study Areamentioning
confidence: 98%
“…analysis. In the study area, it is assumed that surficial groundwater levels peak at the same time as mountain snowpack, being around April 1 each year (Barandiaran et al 2017). Prior sewer flow data in the study area consistently indicated a spring high and a fall low.…”
Section: Study Areamentioning
confidence: 98%
“…A recognition of the urgent need for extended snowpack records has resulted in several tree-ring derived reconstructions directly targeting snowpack (Coulthard et al, 2021). These reconstructions exist throughout the western US (Anderson, 2010;Anderson et al, 2012;Barandiaran et al, 2017;Belmecheri et al, 2016;Brice et al, 2021;Harley et al, 2020;Lepley, 2018;Pederson et al, 2011;Timilsena & Piechota, 2008;Thornton, 2018;Touchan et al, 2021;Tunnicliff, 1975;C. A. Woodhouse, 2003).…”
Section: Tree-ring Based Snowpack Reconstruction In Oregonmentioning
confidence: 99%
“…A recognition of the urgent need for extended snowpack records has resulted in several tree‐ring derived reconstructions directly targeting snowpack (Coulthard et al., 2021). These reconstructions exist throughout the western US (Anderson, 2010; Anderson et al., 2012; Barandiaran et al., 2017; Belmecheri et al., 2016; Brice et al., 2021; Harley et al., 2020; Lepley, 2018; Pederson et al., 2011; Timilsena & Piechota, 2008; Thornton, 2018; Touchan et al., 2021; Tunnicliff, 1975; C. A. Woodhouse, 2003). In Oregon, tree‐ring derived reconstructions document ongoing hydroclimate shifts in Upper Klamath Basin water year precipitation (Malevich et al., 2013), Columbia River Basin streamflow (Littell et al., 2016), Crater Lake water levels (D. L. Peterson et al., 1999), and Central Oregon soil moisture (Pohl et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Details of these stations are shown in Figure 1 and Table 2. Previous studies have reconstructed the historical snow water equivalent (SWE) series using the April 1 SWE, which was considered as the annual maximum SWE [49,50]. The November-April SWE was also confirmed for SWE reconstruction [51].…”
Section: Remotely Sensed Snow Depth Data and Climate Response Analysi...mentioning
confidence: 99%